(untitled) (Research, Society and Development, 2021)
Fusion is a dental anomaly characterized by the union of two tooth germs. Supernumerary teeth are elements that develop beyond normal dentition. The combination of these two deviations from normal standards makes diagnosis challenging. These anomalies can result in serious problems in dentition development if they are not diagnosed and treated early. After a correct diagnosis, the dental surgeon must evaluate all parameters and decide on the best treatment approach. Tooth removal is often indicated when it presents with complications or any associated pathology. The objective is to report a case of a mandibular third molar fused with a supernumerary, discuss these anomalies, as well the prevalence, management, and discussion of the subject. This is a case report, of the descriptive qualitative type, based on the scientific literature. The literature shows that the fusion between a supernumerary and another element is a rare condition, and in some cases, endodontic treatment can be chosen, but in others surgical treatment is feasible. In the case reported here, we opted for surgical removal of the element to prevent impaction of the tooth when fully developed, which would make the treatment even more difficult. We conclude that monitoring the evolution of third molars should be done early to observe their formation process and diagnose any anomaly that may arise, to resolve it early and avoid further consequences. Furthermore, we emphasize the importance of CBCT in differential diagnosis and in obtaining information for surgical planning.